Macroeconomic implications of financial imperfections: A survey - Stijn Claessens; M. Ayhan Kose (Koç University-TÜSİAD Economic Research Forum (ERF), 2017)
This paper surveys the theoretical and empirical literature on the macroeconomic implications of financial imperfections. It focuses on two major channels through which financial imperfections can affect macroeconomic outcomes. The first channel, which operates through the demand side of finance and is captured by financial accelerator-type mechanisms, describes how changes in borrowers' balance sheets can affect their access to finance and thereby amplify and propagate economic and financial shocks. The second channel, which is associated with the supply side of finance, emphasises the implications of changes in financial intermediaries' balance sheets for the supply of credit, liquidity and asset prices, and, consequently, for macroeconomic outcomes. These channels have been shown to be important in explaining the linkages between the real economy and the financial sector. That said, many questions remain.
Keywords: D53; E21; E32; E44; E51; F36; F44; F65; G01; G10; G12; G14; G15; G21; 330; Asset prices; balance sheets; credit; financial accelerator; financial intermediation; financial linkages; international linkages; leverage; liquidity; macro-financial linkages; output; real-financial linkages